Social predictors of marijuana use among African American youth - Hollar, Madison K (Journal of addictions & offender counseling, 2023)
As marijuana use is increasingly decriminalized in the United States, the research suggests that understanding the importance of risk and protective factors within each racial/ethnic group is key to buffering the impact marijuana has on youth. Therefore, the current study examined the potential impacts of psychosocial factors included in the Theory of Planned Behavior—perceived risk, peer disapproval, and parental involvement—on marijuana use in a nationally representative sample of African American youth (n = 1768). Increased perceived risk, peer disapproval, and parental involvement were each associated with lower rates of last year marijuana use. Implications for prevention and treatment are discussed.